Beyond the Northwest Forest Plan - Ariadno, Melda Kamil (UI Scholars Hub, 2021)
The United States of America be the main actors in the wood industry. That condition has become a burden by the government of the United States of America because the increase the pressure from the expert in the environmental field, which more support do the reforestation rather than deforestation. The changing role from the main wood exporter to the main wood importer, caused the national market of the United States of America get a loss, like raise the price of wood product. The conflict between the United States of America with Canada related to wood product become a concern by the stakeholders, and made Bush’s government make a new wood policy which regulates the reforestation and healthy forest programme. This article is trying to discuss the situation about the United States of America’s policy in wood production.